PRELIMINARY OBSERVATIONS ON THE SPAWNING OF INDIAN CARPS, INDUCED BY INJECTION OF PITUITARY HORMONES - K H, Alikunhi; M A, Vijayalakshmanan; K H, Ibrahim (Indian Journal of Fisheries, 2015)
The cultivated and cultivable species of Indian carps generally breed in riverine habitats and, for rearing and stocking in ponds, their tiny young ones are collected in millions from the major rivers every year, during the monsoon months, June-August. These collections, however, invariably comprise a mixture of several species, a good many of which are unsuitable or undesirable for cultivation in ponds. As there is, at present, no dependable method for segregating the unwanted fish fry from the wanted ones at the early stage at which they are collected, the fish farmer is now obliged to rear the mixed lot of fry in nursery ponds and remove the unwanted species only when they have grown^ap to a distinguishable size. Considerable nursery space and appreciable expenditure for preparing the same have thus to be wasted for rearing these unwanted fry.